Development of Primary Energy for the Nation (International Journal of Innovative Research in Engineering & Management, 2021)
The present research emphasizes upon the utilization of  alternative renewable energy sources, mainly solar energy, to  fulfil the energy demand in buildings. The article includes a  review of the literature on the kinds of field data required,  parameters for energy-efficient structures, estimate of solar  energy production on buildings, techno-economic analysis,  and viability of Building Integrated Photovoltaics (BIPV).  The team's results in both instances indicate that retrofitting  BIPV in an existing structure is costlier than designing a  building with BIPV in mind. In addition, BIPV modules  offered great architectural shape and enhanced the building's  overall aesthetics. The BIPV has been shown to be cost  efficient since it not only generates energy but also reduces  the cost of the construction materials it replaces. We estimate  the payback period for BIPV to be 60-180 months, depending  on the kind of connection, the quantity of energy replaced by  BIPV, as well as existing government policies regarding  incentives.
Keywords: Building Integrated Photovoltaics (BIPV); Economic Payback; Primary Energy; Retrofitting; Self-Sufficient Building